Proton conducting membranes based on Poly(2,5-benzimidazole) (ABPBI)-Poly(vinylphosphonic acid) blends for fuel cells - Acar, Oktay; Sen, Unal; Bozkurt, Ayhan; Ata, Ali (Pergamon-Elsevier Science Ltd, 2009)
Polymer electrolyte membranes (PEM) were fabricated by blending of Poly(2,5-benzimidazole) (ABPBI) and Poly(vinylphosphonic acid) (PVPA) at several stoichiometric ratios with respect to monomer repeating units. The characterization of the membranes were carried out by using Fourier-transform infrared spectroscopy (FT-IR) for inter-polymer interactions, scanning electron microscope (SEM) for surface morphology as well as homogeneity and thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) for thermal properties. Water uptake measurements were made to investigate the swelling character the blends that was changed with PVPA composition. The spectroscopic measurements and water uptake studies suggested the complexation between ABPBI and PVPA that inhibited dopant exclusion up on swelling in excess water. Proton conductivities of the hydrated and anhydrous samples were measured using impedance spectroscopy. Although the proton conductivity of the blends was lower in the anhydrous state such as 1.8 x 10(-6) S/cm at 150 degrees C for ABPBLPVPA with (1:2), it increased to 0.004 S/cm for ABPBI:PVPA (1:4) at 20 degrees C (RH = 50%). (C) 2009 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: Poly(2,5-benzimidazole); Poly(vinylphosphonic acid); Blend; Proton conductivity; Fuel cell